OSMOTIC PERFORMANCE AND GROWTH RATE OF STRIPED CATFISH (Pangasianodon hypohthalmus) AT DIFFERENT SALINITY - Riswan, M; Syawal, Henni; Tang, Usman M (Asian Journal of Aquatic Sciences, 2022)
The aim of this study was to analyze the effects of different salinities on osmotic performance rate, growth performance, and oxygen consumption rate Pangasianodon hypophthalmus. The method used is an experimental method by applying a completely randomized design (CRD) with four treatments, salinity 0 ppt, salinity 5 ppt, salinity 7 ppt, and salinity 9 ppt. The fish specimen used is 8 cm in length, weighing 4 g, were raised in a 54 L tank containing 40 L of water at a density of 1 fish 2 L-1 and kept for 45 days. Feed with commercial pellet 3 times a day in at satiation. The treatment with 5 ppt salinity showed the best effects, yielding an osmotic performance rate of 21,66 mOsm/I H2O, absolute weight growth of 9,63 g, the absolute length of 3.54 cm, the specific growth rate of 2,99 %, the oxygen consumption rate of 0,410 mgO2/g body weight/hour and survival rate 100 %. The water quality is at a level suitable for the growth of P. hypophthalmus. It was concluded that 5 ppt salinity can minimize the value of the osmotic performance rate, increase growth rates, minimize the level of oxygen consumption and increase.